1993
DOI: 10.1016/0014-5793(93)81484-h
|View full text |Cite
|
Sign up to set email alerts
|

The point mutation of mitochondrial DNA characteristic for MERRF disease is found also in healthy people of different ages

Abstract: The A-to-G transition mutation in the tRNALy" gene of mitochondrial DNA (mtDNA), characteristic for the maternally inherited MERRF syndrome (myoclonic epilepsy with ragged red fibers), has been identified by point mutation-specific polymerase chain reaction in extraocular muscle from I1 of 16 healthy people of different ages. No mutation was found in navel-string samples from 5 newborns, in HeLa cells, and in 2 individuals younger than 20 years. On the other hand, the mutation is present in all 5 tested 7C89-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(51 citation statements)
references
References 25 publications
2
49
0
Order By: Relevance
“…Many studies have focused on the levels of specific point mutations found previously in cases of mtDNA disease, such as A3243G (Liu et al ., 1998) or A8344G (Münscher et al ., 1993). Some of these mutations have been previously suggested to lie in mutational hotspot regions.…”
Section: Mtdna Point Mutations and Agingmentioning
confidence: 99%
“…Many studies have focused on the levels of specific point mutations found previously in cases of mtDNA disease, such as A3243G (Liu et al ., 1998) or A8344G (Münscher et al ., 1993). Some of these mutations have been previously suggested to lie in mutational hotspot regions.…”
Section: Mtdna Point Mutations and Agingmentioning
confidence: 99%
“…A-G; nt 4317, tRNA Ile , A-G; nt 5692, tRNA Asn , A-G; nt 8344, tRNA Lys , G-A; nt 10006, tRNA Gly , A-G; and 12246, tRNA Ser , A-G, Preparation of mtDNA Probes by point mutation specific PCR as previously described 30,31,59 on 18 microdissected probes of 6 formalin-fixed paraffin-embedded livers Specific probes of mtDNA (G1, G2, G3, Fig. 1) were produced by polymerase chain reaction (PCR) for in situ hybridization.…”
Section: In Situ Hybridizationmentioning
confidence: 99%
“…tions and more than 40 point mutations of mtDNA have been identified, 118,147,148 which may even coexist 30,31,149 the In situ hybridization and PCR studies in skeletal muscle have revealed that the mutated mtDNA molecules accumu-involvement of other mutations of mtDNA needs further elucidation. late in the respiratory deficient cells, [56][57][58] causing the enzyme defect when a certain threshold of mutated DNA is In summary the results show that defects of the respiratory chain represent a general phenomenon affecting not only reached.…”
Section: Aidmentioning
confidence: 99%
See 1 more Smart Citation
“…Persistence of this damage would be expected to cause a high mutation rate in mtDNA. Thus, it is not surprising that mutations, including deletions, duplications, and point mutations, have been found to accumulate in mtDNA in a variety of tissues during aging in humans, monkeys, and rodents (68)(69)(70)(71)(72)(73) and cause a mosaic pattern of respiratory chain deficiency in pre-and post-mitotic tissues. The most frequent and best characterized age-associated mtDNA mutation is a 4977-bp deletion also called the "common deletion".…”
Section: Mitochondrial Dna Repair and Agingmentioning
confidence: 99%